A Multi-Bioinspired Dual-Gradient Electrode for Microbubble Manipulation toward Controllable Water Splitting - Long, Zhiyun (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2020 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.